Cigarettes and Its Effects on Health - Balatif, Ridwan (Talenta Publisher, 2020)
Background: One of the biggest challenges in the world of health is the problem of smoking. In 2018, there was an increase in smokers at the age of 10-18 years by 9.1% compared to 2013, which was 7.2%. It is feared that the increasing number of smokers at a young age will increase the number of non-communicable diseases (NCD) at a young age. Methods: Writing this article uses the method of literature searching from various sources of information including e-books, websites and search engines. The e-books used contain cigarette information and its effects on health, the websites used are the website of the government and WHO to search for prevalence data and other information, and the search engines used are Google Scholar and Pubmed to search information on cigarette content research and its effects on health. Discussion: The content of cigarettes can cause various side effects in almost all organs of the body. Various studies have found that smoking is a risk factor for NCD. Conclusion: Cessation of smoking can save sufferers and also save people around smokers. When a smoker starts quitting smoking, the body will undergo the process of cleaning up toxic substances of cigarettes that have entered the body. Keywords: cigarette, literature searching, NCD Â Â Latar Belakang: Salah satu tantangan terbesar dalam dunia kesehatan ialah masalah rokok. Pada tahun 2018, terjadi peningkatan perokok pada usia 10-18 tahun sebesar 9,1% dibandingkan pada tahun 2013 sebesar 7,2%. Peningkatan jumlah perokok di usia muda ini dikhawatirkan akan meningkatkan jumlah Penyakit Tidak Menular (PTM) di usia muda. Metode: Penulisan artikel ini menggunakan metode pencarian literatur dari berbagai sumber informasi berupa e-book, website dan search engine. E-book yang dipakai memuat informasi rokok dan pengaruhnya kekesehatan, website yang dipakai adalah website pemerintah dan WHO untuk pencarian data prevalensi dan informasi lainnya, dan search engine yang dipakai adalah Google Scholar dan Pubmed untuk pencarian informasi penelitian kandungan rokok dan pengaruhnya kepada kesehatan. Pembahasan: Dari hasil pencarian, kandungan pada rokok dapat menimbulkan berbagai efek samping hampir di seluruh organ tubuh. Berbagai penelitian mendapatkan bahwa kebiasaan merokok merupakan faktor risiko terjadinya PTM. Kesimpulan: Penghentian kebiasaan merokok ini dapat menyelamatkan penderitanya dan juga menyelamatkan orang di sekitar perokok. Ketika seorang perokok mulai berhenti untuk merokok, maka tubuh akan melakukan proses pembersihan dari zat racun pada rokok yang sudah masuk ke dalam tubuh. Kata kunci: rokok, PTM, pencarian literatur